EUROPEANIZATION OF THE BALKANS, OR BALKANIZATION OF EUROPE? - Vasko Naumovski (Georgetown University, 2019)
The European Union enlargement process has been the greatest benefits for European citizens and has proven to be the most successful project of transition of the post-communist countries. Nevertheless, the Balkans region remains without a clear perspective for full integration into the EU, creating potential for further uncertainties and even conflicts. The lack of vision to end the bilateral disputes in the region, as well as the absence of an exit strategy to enable self-sustainability of some of the societies, requires greater attention and efforts to contain the ‘Powder Keg of Europe’.
Keywords: Balkans, European Union, Enlargement, Balkanization, Europeanization.